Inadverted Perforation of Trachea: An Enigma or A Challenge - García, Giselle Castillo; Moreno, Julio César Barajas; Rosas, Juan Rubén Trejo; Roehrich, Omar Cáceres Von; Ordónez, Juan Carlos Hernández; Salvador, Judá Raquel Hernández; Jiménez, Alejandro Altamirano; González, Mireya De La Fuente; Sánchez, Morelos Adolfo García; Viloria, Nancy Adelina Velasco (British Journal of Healthcare and Medical Research, 2023)
Introduction: traumatic injuries to the respiratory tract are rare, only a small portion of the trachea is unprotected above the manubrium sternalis, exposing the neck. The incidence is low and mortality is very high, higher than 82%. Objective: report of a case and analysis of the literature. Case reports: 46-year-old male who was admitted to the emergency room with four gunshot wounds to the thorax and extremities, vital signs: T/A: 139/36 mm Hg. HR: 107 bpm. RF: 20rpm. Temp 36.9°C. Sat 97%. Glasgow 6 points, neck with increased volume at the expense of subcutaneous emphysema, predominantly on the right, which extends to both hemithorax. Discussion: the clinical presentation of this pathology is non-specific. They present with generalized subcutaneous soft tissue emphysema, explosive and overwhelming, pneumomediastinum and/or pneumothorax. Other added signs may be respiratory failure, hemoptysis, or shock. The specific diagnosis is bronchoscopic but the most sensitive study is computed tomography, it is necessary to have the adequate inputs or resources, as well as the expertise of multidisciplinary personnel. Endoscopic treatment is the primary approach with a success rate of 50%; however, if it fails or is not feasible, early surgical treatment is mandatory. Conclusions: tracheal perforations are so complex that they require multidisciplinary management, with a third level medical care infrastructure. Surgery is the mainstay in resolving treatment in emergency or elective cases, its delay is a catastrophic outcome for the patient.